Cytokine Profiles of Head and Neck Squamous Cell Carcinoma Undergoing Dual Immunotherapy With Cetuximab and Pembrolizumab Identify Interferon Gamma-Induced Protein 10 as Novel Biomarker - Berszin, Michael; Michaelides, Ioannis; Siemert, Julia; Röhl, Louisa; Wellhausen, Jana; Wald, Theresa; Bohr, Christopher; Künzel, Julian; Gradistanac, Tanja; Dietz, Andreas; Zebralla, Veit; Pirlich, Markus; et al. (Frontiers in Oncology, 2022)
Background Pembrolizumab and cetuximab are antibodies under investigation in head and neck squamous cell carcinoma (HNSCC) either as single agents or combined with cisplatin and other chemotherapeutic drugs, e.g., 5-fluorouracil and/or docetaxel. However, also the combination of both antibodies may have potential in recurrent/metastatic (R/M) HNSCC, in particular in cisplatin-resistant or -refractory cases or patients with comorbid disease, e.g. patients with impaired renal function. Methods To clarify potential benefit that may result from such combination, we used the FLAVINO assay, a short-time ex vivo assay to compare responsiveness of HNSCC to pembrolizumab, cetuximab and both combined regarding colony formation of epithelial cells of biopsy-derived tumor samples and their cytokine production within three days either without or with stimulation with 10 ng/mL interferon gamma (IFN-γ). Vascular endothelial growth factor A (VEGF), monocyte chemoattractant protein 1 (MCP-1 or CCL2), interleukin 6 (IL-6), IL-8, IFN-γ, and interferon gamma-induced protein 10 (IP-10 or CXCL10) in supernatants were measured by ELISA. Results We detected huge heterogeneity in response to cetuximab, pembrolizumab and both combined with and without IFN-γ stimulation. Moreover, we detected a link between IFN-γ induced IP-10 release and improved outcome in those HNSCC patients who were capable to respond to IFN-γ and pembrolizumab, cetuximab and both combined with a further increase in IP-10 production. We derived an “IP-10 score” that independent from clinical characteristics of HNSCC patients and therapy regimens applied was able to predict their outcome. Conclusions The heterogeneity in the ex vivo response of cetuximab, pembrolizumab and both combined with and without IFN-γ stimulation identifies subgroups of HNSCC patients with deviating OS.